A rationale for early extracorporeal membrane oxygenation in patients with postinfarction ventricular septal rupture complicated by cardiogenic shock. (May 2017) - Rob, Daniel; Špunda, Rudolf; Lindner, Jaroslav; Rohn, Vilém; Kunstýř, Jan; Balík, Martin; Rulíšek, Jan; Kopecký, Petr; Lipš, Michal; Šmíd, Ondřej; Kovárník, Tomáš; Mlejnský, František; et al.
Abstract: Aims: Ventricular septal rupture (VSR) became a rare mechanical complication of myocardial infarction in the era of percutaneous coronary interventions but is associated with extreme mortality in patients who present with cardiogenic shock (CS). Promising outcomes have been reported with the use of circulatory support allowing haemodynamic stabilization, followed by delayed repair. Therefore, we analysed our experience with an early use of Veno‐Arterial Extracorporeal Membrane Oxygenation (V‐A ECMO) for postinfarction VSR. Methods and results: We conducted a retrospective search of institutional database for patients presenting with postinfarction VSR from January 2007 to June 2016. Data from 31 consecutive patients (mean age 69.5 ± 9.1 years) who were admitted to hospital were analysed. Seven out of 31 patients with VSR who were in refractory CS received V‐A ECMO support preoperatively. ECMO improved end‐organ perfusion with decreased lactate levels 24 hours after implantation (7.9 mmol/L vs. 1.6 mmol/L, p = 0.01), normalized arterial pH (7.25 vs. 7.40, p < 0.04), improved mean arterial pressure (64 mmHg vs. 83 mmHg, p < 0.01) and lowered heart rate (115/min vs. 68/min, p < 0.01). Mean duration of ECMO support was 12 days, 5 out of 7 patients underwent surgical repair, 4 were weaned from ECMO, 3 survived 30 days and 2 survived more than 1 year. The most frequent complication (5 patients) and the cause of death (3 patients) was bleeding. Conclusions: Our experience suggests that early V‐A ECMO in patients with VSR and refractory CS might prevent irreversible multiorgan failure by improved end‐organ perfusion. Bleeding complications remain an important limitation of this approach.